(untitled) (Research, Society and Development, 2021)
The Itacaiúnas hydrographic sub-region has undergone significant changes over the years, due to the replacement of forest areas by pasture, which makes the territory vulnerable and with high potential for environmental fragility. This study aims to analyze the dynamics of environmental fragility of the Itacaiúnas Hydrographic Sub-Region (SRHI) for purposes of environmental planning. The research was based on the use of remote sensing to survey the variables and the allocation of weights for the elaboration of fragility maps related to the classes of slope, pedology, geomorphology and land use and occupation over the years 1985, 1995, 2005 and 2018. The results indicated that human conditions depreciate natural conditions, since the very low class of fragility occupied 46.9% of the total area in 1985 was replaced by the middle class and started to occupy 48.6% in 2018 Thus, it was observed that the Parauapebas River Basin (BRP) showed a higher degree of fragility, while the Catete River Basin (BRC) Sororó River Basin (BRS) and Rio Vermelho Basin (BRV) were less fragile, indicating to be the main change in SRHI. In this sense, it is concluded that the area under study was shown to be vulnerable in relation to ecodynamics, as it presents a medium degree of fragility in its majority, which shows the need for improvements in terms of environmental planning.